Scanning, Contextual Factors, and Association With Performance in English Premier League Footballers: An Investigation Across a Season - Jordet, Geir; Aksum, Karl Marius; Pedersen, Daniel N.; Walvekar, Anup; Trivedi, Arjav; McCall, Alan; Ivarsson, Andreas; Priestley, David (Frontiers in Psychology, 2020)
Scanning in football (soccer) denotes an active head movement where a player’s face is temporarily directed away from the ball to gather information in preparation for subsequently engaging with the ball. The aim of this study was to learn more about the ways which 27 elite professional football players in an English Premier League club use scanning in competitive matches, the conditions under which this behavior is exhibited, and the relationships between these behaviors and performance. Players were filmed across 21 matches, producing a total number of 9 574 individual ball possessions for analysis. Close-up video analyses of scanning show positional differences (with central midfielders and central defenders scanning most frequently, forwards least) and contextual differences (with relatively lower scanning frequency in situations with tight opponent pressure, in positions wide in the field and closer to the opponent's goal, and under certain game state conditions). Players scan more frequently prior to giving passes than when they dribble, shoot or only receive it, as well as prior to more progressive/forward passes compared to less progressive/backward ones. A Bayesian hierarchical model, that accounts for individual player differences and pass difficulty, shows that the more a player scans the higher the probability of completing a pass. In conclusion, match demands are likely to constrain the extent to which highly elite players scan, and scanning seems to have a small, but positive role in elite football players’ performance.